The Influence of Organizational Communication, Work Motivation on Lecturer Performance at the Faculty of Management and Business Culture, Mandalika Education University (UNDIKMA) - Wulandari, Yayang Erry (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is aimed at analyzing and determining the significant effect of organizational communication and work motivation on the performance of lecturers in Faculty of Culture Management and Bisiness , Undikma as well as  determining which of the variables is the most dominantly affecting the performance of lecturers in Faculty Culture Management and Business. This research is associative or causality study. The respondents were all 59 in this Faculty. The data were analyzed with multiple linear regression using SPSS Program. The research showed that 1) Organisational communication variable had positive and significant effect on the performance of lecturers in Faculty Culture Management and Business, 2) Work Motivation variable had positive and significant effect on the performance of lecturers in Faculty Culture Management and Bisiness, and 3) Organisational Communication variable had the most dominant effect on the performance of lecturers in Faculty Culture Management and Business Based on these findings, it is recommended that Faculty management improves the level of effective communication and work motivation to improve the level of working performance. It also directs future research to cope with other variables such as the university leaders’ perspectives to triangulate the findings.